Combined effects of adsorption and photocatalysis by hybrid TiO2/ZnO-calcium alginate beads for the removal of copper - Kanakaraju, Devagi; Ravichandar, Shantini; Ying, Chin Lim (Chinese Academy of Sciences, 2016)
The use of nanosized titanium dioxide (TiO2) and zinc oxide (ZnO) in the suspension form during treatment makes the recovering and recycling of photocatalysts difficult. Hence, supported photocatalysts are preferred for practical water treatment applications. This study was conducted to investigate the efficiency of calcium alginate (CaAlg) beads that were immobilized with hybrid photocatalysts, TiO2/ZnO to form TiO2/ZnO-CaAlg. These immobilized beads, with three different mass ratios of TiO2:ZnO (1:1, 1:2, and 2:1) were used to remove Cu(II) in aqueous solutions in the presence of ultraviolet light. These beads were subjected to three cycles of photocatalytic treatment with different initial Cu(II) concentrations (10-80ppm). EDX spectra have confirmed the inclusion of Ti and Zn on the surface of the CaAlg beads. Meanwhile, the surface morphology of the beads as determined using SEM, has indicated differences of before and after the photocatalytic treatment of Cu(II). Among all three, the equivalent mass ratio TiO2/ZnO-CaAlg beads have shown the best performance in removing Cu(II) during all three recycling experiments. Those TiO2/ZnO-CaAlg beads have also shown consistent removal of Cu, ranging from 7.14-62.0ppm (first cycle) for initial concentrations of 10-80ppm. In comparison, bare CaAlg was only able to remove 6.9-48ppm of similar initial Cu concentrations. Thus, the potential use of TiO2/ZnO-CaAlg beads as environmentally friendly composite material can be further extended for heavy metal removal from contaminated water